Investigating Online Shopping Satisfaction: A Special Study of Amazon’s Customer Experience - N. A. Arshiya Afrin, S. L. Sobiya (Journal of Informatics Education and Research, 2024)
In this study, the researcher mainly focuses on establishing the role of customer satisfaction with online shopping with special focus to Amazon shopping platform.The primary objective of this study is to know why customers prefer to shop with Amazon and what/who influences consumer behavior towards Amazon.The statistical tools used for this study is factor analysis with the help of Kaiser-Meyer-Olkin (KMO) Measure and Bartlett's Test of Sphericity.Were as, data is collected by circulating questionnaires to the customers who do online purchase. Whereas, secondary data is compiled with the help of many research journals, articles, and books. For this research study a sample size of 83 is considered for measuring the replies from the selective respondents. Some of the important suggestion and recommendation from this paper can be concluded as Enhance Training Programs,Maintain Accurate Product Descriptions,Optimize Website Performance.By exploring various avenues, future research can be enhance to intricate the relationship between online shoppers and consumer satisfaction, resulting in more effective strategies for businesses and policymakers.